CONTROL OF THIN COVERINGS ON EXTENSIVE SAMPLES BY MEANS OF ATOMIC EMISSIVE SPECTRAL ANALYSIS - A. G. Nepokojchitsky; K. V. Frantskevich; S. G. Astashenko (Литьë и металлургия)
The way of the coverings parameters control on different extensive objects using atomic emissive spectral analysis is described. The device for realization of this method is developed. The control of the composition and uniformity of brass covering on cord wire is demonstrated as an example of practical application of the offered way and developed for its realization device.